Local anesthetic infiltration and its points of application in the treatment of nummular headache: Case Report - Knak, Caroline (Headache Medicine, 2024)
Introduction Nummular headache is a rare condition, and it is often difficult to control with therapies used to manage pain. It is known that the use of local anesthetic is a possibility as prophylaxis, but, until now, there is no description of which points should be infiltrated in the affected region. Objective In this case report we describe, for the first time, a possible technique to be used in the application of local anesthetic in patients with nummular headache, in the painful area. Case Report A 73-year-old woman came for evaluation due to a headache that had started four months ago. The pain was acute, of strong intensity, located in the right parieto-occipital region, rounded in shape and measuring 1,9685 inches in diameter. The attacks were interspersed with asymptomatic periods, lasted an average of 5 minutes, and were described as a burning sensation and shock, followed by pre-syncope or even syncope after intense pain. During physical examination, the patient reported a burning sensation when touched in the area of ​​pain (dysesthesia), without other changes. Laboratory tests, cerebral magnetic resonance imaging and intracranial arterial angiography were requested, all with results within normal limits. After attempts to use gabapentin and indomethacin, drugs not tolerated by the patient even in subdoses due to adverse effects, blockage of greater and lesser occipital nerves ipsilateral to the pain, associated with the application of bupivacaine without vasoconstrictor (0.5 ml/point) in the affected region were done. The technique used in the coin-shaped area was carried out using five infiltration points, one in the central region and the others distributed in the periphery. The patient reported having no headaches at the first reassessment (carried out 2 weeks after the procedure), and remained headache-free for the 6-month period during which she was monitored. Conclusion Local anesthetic infiltration should be considered in patients with nummular headache. The technique described above is easily applicable, has a lower cost, as well as low potential for side effects.